Penerapan PBL dalam Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP Kelas VII: Penelitian - Ripaldo Pandiangan; Imelda Sihombing (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to enhance the problem-solving abilities of seventh-grade students (Class VII-6) at SMPN 9 Medan during the 2024/2025 academic year, specifically in their understanding of circle geometry. To achieve this, the (PBL approach was implemented as part of a Classroom Action Research (CAR) design, which was carried out in two cycles: Cycle I and Cycle II.To assess students' progress, the study used pre-tests, post-tests for Cycle I, and post-tests for Cycle II as evaluation tools. The collected data was analyzed using descriptive statistics, allowing for a comparison of students' problem-solving abilities over time. The results indicate a consistent improvement in students' individual and class-wide problem-solving performance between Cycle I and Cycle II. Based on these findings, the study concludes that Problem-Based Learning (PBL) effectively enhances students' ability to solve mathematical problems, particularly in the context of circle geometry, among seventh-grade students at SMPN 9 Medan